2017
DOI: 10.1038/nn.4491
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic CRFR1 is essential for HPA axis regulation following chronic stress

Abstract: The hypothalamic-pituitary-adrenal axis is a pivotal component of an organism's response to stressful challenges, and dysfunction of this neuroendocrine axis is associated with a variety of physiological and psychological pathologies. We found that corticotropin-releasing factor type 1 receptor within the paraventricular nucleus of the hypothalamus is an important central component of hypothalamic-pituitary-adrenal axis regulation that prepares the organism for successive exposure to stressful stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 22 publications
3
79
0
Order By: Relevance
“…Above we considered evidence from reporter mice and functional studies that support presynaptic receptor expression in the central nucleus of the amygdala as a potential way to reconcile discrepant site‐of‐action and cellular (mRNA) localization data at this locus. Similarly, stress‐related functional data have recently been provided to support indications from reporter mice of cellular CRF 1 expression in the paraventricular nucleus of the hypothalamus (Justice et al, ; Ramot et al, ). Neither the central nor the paraventricular nucleus exhibited detectable [ 125 I]‐PD‐Svg binding in the present experiments, making it difficult to view as decisive our failure to resolve radioligand binding in any of the other areas of structure‐function mismatch among the central autonomic structures listed above.…”
Section: Discussionmentioning
confidence: 91%
“…Above we considered evidence from reporter mice and functional studies that support presynaptic receptor expression in the central nucleus of the amygdala as a potential way to reconcile discrepant site‐of‐action and cellular (mRNA) localization data at this locus. Similarly, stress‐related functional data have recently been provided to support indications from reporter mice of cellular CRF 1 expression in the paraventricular nucleus of the hypothalamus (Justice et al, ; Ramot et al, ). Neither the central nor the paraventricular nucleus exhibited detectable [ 125 I]‐PD‐Svg binding in the present experiments, making it difficult to view as decisive our failure to resolve radioligand binding in any of the other areas of structure‐function mismatch among the central autonomic structures listed above.…”
Section: Discussionmentioning
confidence: 91%
“…We then investigated how sympathetic activation at the specific vessels under stress condition is regulated. It is reported that PVN neurons include TH+ neurons are activated by several stresses, especially chronic ones ( Herman and Cullinan, 1997 ; Ramot et al, 2017 ; Shi et al, 2013 ; Ulrich-Lai and Herman, 2009 ). Consistent with these results, we found that PVN TH+ neurons were specifically activated by stress condition even without EAE induction ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…All behavioral paradigms were performed as previously described 24 26 with modifications. For a detailed description of the behavioral tests, see SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…In situ hybridization 27 29 and immunohistochemistry 26 , 30 were performed as described. For a full description of the protocols and antibodies used, see SI Methods.…”
Section: Methodsmentioning
confidence: 99%